The Role and Interactions of Programmed Cell Death 4 and its Regulation by microRNA in Transformed Cells of the Gastrointestinal Tract - Ferris, William Frank (Frontiers in Oncology, 2022)
Data from GLOBOCAN 2020 estimates that there were 19.3 million new cases of cancer and 10.0 million cancer-related deaths in 2020 and that this is predicted to increase by 47% in 2040. The combined burden of cancers of the gastrointestinal (GI) tract, including oesophageal-, gastric- and colorectal cancers, resulted in 22.6% of the cancer-related deaths in 2020 and 18.7% of new diagnosed cases. Understanding the aetiology GI tract cancers should have a major impact on future therapies and lessen this substantial burden of disease. Many cancers of the GI tract have suppression of the tumour suppressor PDCD4 and this has been linked to the expression of microRNAs which bind to the untranslated region of PDCD4 mRNA and either inhibit translation or target the mRNA for degradation. This review highlights the properties of PDCD4 and documents the evidence for the regulation of PDCD4 expression by microRNAs in cancers of the GI tract.